Developing A Robot to Improve The Accuracy of Ring Retrieval and Throwing at The ABU Robocon Indonesia Robot Competition - Siswoyo, Agus (Universitas Sanata Dharma, 2023)
This article outlines the creation and application of a technologically improved robot designed to amplify the precision and effectiveness of ring retrieval and projection tasks in the ABU Robocon Indonesia Robot Challenge. The ABU Robocon competition is an annual event that tasks teams with crafting robots capable of accomplishing specific assignments under a predetermined time limit. The ring retrieval and projection task, historically known for its precision requirements, has proven to be quite demanding. Our strategy entailed the incorporation of cutting-edge technologies into the robot's design, encompassing computer vision and machine learning algorithms, to augment its accuracy and performance. We equipped the robot with cameras and sensors for the detection and analysis of ring positions and orientations. Real-time decisions regarding the optimal approach for retrieving and accurately projecting the rings were made using machine learning models that had undergone training. The outcomes of our experiments reveal a marked enhancement in the robot's performance when compared to conventional methods. The tech-enhanced robot consistently exhibited a heightened success rate when performing ring retrieval and projection tasks. This development not only boosts the competitiveness of our robot in the ABU Robocon competition but also underscores the potential of advanced technologies in enhancing the performance of robotics systems when confronted with intricate tasks.